PELATIHAN DESAIN GRAFIS DENGAN CANVA: MENINGKATKAN EFEKTIVITAS PUBLIKASI INSTANSI PEMERINTAH - Kirman, Kirman; M Hafiz Pebriansyah; Alvi ADN Nasir Chan; Pemo Marzoni; Ahmad Fauzi; Rahmat Karindra (Kohesi: Jurnal Sains dan Teknologi, 2025)
As digital technology advances, government agencies are increasingly encouraged to master graphic design skills to make their publications and promotions more effective. However, many employees still lack expertise in this area. Therefore, as part of their Field Work Practice (PKL), students from Universitas Muhammadiyah Bengkulu conducted graphic design training for employees of the Bengkulu Provincial Industry and Trade Office (Disperindag) using Canva. Canva was chosen for its ease of use, ready-to-use templates, and ability to create professional designs without requiring complex technical skills. The training included basic graphic design materials, demonstrations of how to use Canva, and hands-on practice sessions supervised by the trainer. Evaluation results showed that participants' understanding and ability to use Canva increased significantly. Many employees who were previously unfamiliar with graphic design now feel more confident in creating attractive and professional designs. Hopefully, this training will help agency employees maximize the use of digital technology to support their work.